2007
DOI: 10.1016/s0828-282x(07)70858-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of clinical efficacy and bleeding risk with intravenous glycoprotein IIb/IIIa antagonists for percutaneous coronary intervention

Abstract: Treatment with GP IIb/IIIa inhibitors in the setting of PCI significantly reduces the rates of 30-day mortality, MI and repeat revascularization procedures. These beneficial effects are achieved at an increased risk of thrombocytopenia and minor bleeding, but not major bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…Within individual meta-analyses, the difference in treatment efficacy between Europe and North America in terms of the most commonly reported fatal endpoint is statistically significant at the 5% level in one meta-analysis [30]. However, given that there are 47 meta-analyses with fatal endpoints, finding one difference that is statistically significant at the 5% level among the 47 differences assessed is not more than would be expected by random chance alone.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Within individual meta-analyses, the difference in treatment efficacy between Europe and North America in terms of the most commonly reported fatal endpoint is statistically significant at the 5% level in one meta-analysis [30]. However, given that there are 47 meta-analyses with fatal endpoints, finding one difference that is statistically significant at the 5% level among the 47 differences assessed is not more than would be expected by random chance alone.…”
Section: Resultsmentioning
confidence: 91%
“…By 'overlapping', it is meant that any one of these meta-analyses shares some trial results with at least one other of these metaanalyses, to the extent that the estimates produced by these meta-analyses may be regarded as being to some degree not independent of one another. For meta-analyses with non-fatal endpoints, there are 23 such overlapping metaanalyses [17,19,20,[26][27][28][30][31][32][33]35,[38][39][40][41][43][44][45][46][47][48][49][50]. Therefore, there are 18 meta-analyses with fatal endpoints [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] and 21 meta-analyses with non-fatal endpoints [15,22,25,42,[52][53]…”
Section: Resultsmentioning
confidence: 99%
“…A later meta-analysis of 21 randomized clinical trials confirmed these results, showing reduced risk of mortality with glycoprotein IIb-IIIa inhibitors at 30 days (OR 0.72, 95% CI 0.56-0.94) and 6 months (OR 0.85, 95% CI 0.68-1.07) [46]. Significant 30-day and 6-month mortality reductions with glycoprotein IIb-IIIa inhibitors were also seen in other meta-analyses [47][48][49].…”
Section: Glycoprotein Iib-iiia Inhibitorsmentioning
confidence: 81%
“…GPIIb/IIIa inhibitors also have been shown to reduce peri-procedural infarction in several clinical trials, a finding confirmed in a meta-analysis [14]. However, in the era of double platelet antiaggregation, GPIIb/IIIa inhibitors are recommended only in high risk patients with intracoronary thrombus [15].…”
Section: Antiplatelet Drugsmentioning
confidence: 91%